Experimental and numerical analysis of wrinkling during forming of multi-layered textile composites. (15th January 2019) - Guzman-Maldonado, E.; Wang, P.; Hamila, N.; Boisse, P.
Abstract: Wrinkling is one of the main flaws that can appear during forming processes of textile composite reinforcements. When the forming is carried out on a multi-layered fabric the wrinkle development is strongly increased if the plies have different orientations. This phenomenon has been observed in previous experimental studies and is confirmed by a set of forming tests on multi-layered reinforcements. Beyond these experiments, a multilayered fabric forming process numerical simulation based on stress-resultant textile shell elements is presented. It is shown that this simulation is able to accurately describe multi-layered fabric forming processes and in particular the development of wrinkles. In the case of multi-layered reinforcements where the neighboring plies are oriented differently, the numerical simulations shows the development of zones where the fibers in one direction are subjected to compression which gives rise to wrinkles. The analysis of the forming for different friction coefficients confirms the major role of the friction between the plies in wrinkling. The influence of the pressure imposed by the blank holder has also been studied.